2016
DOI: 10.12662/2317-3076jhbs.v4i3.860.p174-180.2016
|View full text |Cite
|
Sign up to set email alerts
|

Papilomavírus Humano (HPV) e sua associação entre lesões cervical e anal em mulheres<br>Human papillomavirus (HPV) and its association between cervical and anal injuries in women<br>doi:10.12662/2317-3076jhbs.v4i3.860.p174-180.2016

Abstract: Introdução: Entre as doenças virais sexualmente transmissíveis, a infecção pelo Papilomavírus Humano (HPV) configura-se como a mais comum, e sua incidência vem aumentando acentuadamente nos últimos trinta anos. A infecção anal por subtipos específicos do HPV predispõe o indivíduo à neoplasia intraepitelial anal, que pode evoluir para o câncer de forma similar ao colo uterino. Portanto, o objetivo deste estudo foi avaliar a associação tipo-específica entre infecções anais e cervicais, assim como os aspectos cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
4
4
Order By: Relevance
“…The present study reported for the first time the prevalence and diversity of HPV in anal specimens in HIV-infected women assisted in Belém, Pará, Brazil. Interestingly, we found a low prevalence of anal HPV infection (26.8%) in the examined women, which proved to be much lower than previously reports of anal specimens evaluated in other cities of Brazil, such as Santos [14], Manaus [15], and São Luiz do Maranhão [16], which showed a prevalence of 63%, 79% and 77.7%, respectively. The research of HPV in anal specimen of women infected with HIV-1 is of great importance as the HIV / HPV co-infection may be considered a risk factor for the development of pre-neoplastic lesions in both uterine cervix [17] and the anus [18].…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…The present study reported for the first time the prevalence and diversity of HPV in anal specimens in HIV-infected women assisted in Belém, Pará, Brazil. Interestingly, we found a low prevalence of anal HPV infection (26.8%) in the examined women, which proved to be much lower than previously reports of anal specimens evaluated in other cities of Brazil, such as Santos [14], Manaus [15], and São Luiz do Maranhão [16], which showed a prevalence of 63%, 79% and 77.7%, respectively. The research of HPV in anal specimen of women infected with HIV-1 is of great importance as the HIV / HPV co-infection may be considered a risk factor for the development of pre-neoplastic lesions in both uterine cervix [17] and the anus [18].…”
Section: Discussioncontrasting
confidence: 83%
“…We noticed that most of the participants co-infected with HIV and HPV have had sexual initiation between 10 and 15 years of age (55.2%), similar to that observed in Pernambuco [19]. However, the prevalence of HPV infection was lower than that observed in cervical samples in other cities of Brazil, such as 73.2% [20] and 78.8% [21] in Minas Gerais and 77.7% in Maranhão [16]. We expected a greater prevalence of HIV and HPV co-infection, similar to that found in the city of Manaus (79%), Amazonas' capital, another State of the northern region of Brazil [7].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations